2012
DOI: 10.5194/acp-12-337-2012
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the CO<sub>2</sub> budget of the corn belt: exploring uncertainties from the assumptions in a mesoscale inverse system

Abstract: Abstract. We performed an atmospheric inversion of the CO 2 fluxes over Iowa and the surrounding states, from June to December 2007, at 20 km resolution and weekly timescale. Eight concentration towers were used to constrain the carbon balance in a 1000×1000 km 2 domain in this agricultural region of the US upper midwest. The CO 2 concentrations of the boundaries derived from CarbonTracker were adjusted to match direct observations from aircraft profiles around the domain. The regional carbon balance ends up w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
241
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(248 citation statements)
references
References 55 publications
6
241
1
Order By: Relevance
“…The method used in the paper was described in the study of Lauvaux et al (2012). The state vector (x) that includes the three components described above (daytime fluxes, nighttime fluxes and boundary inflow) is obtained by the following equation:…”
Section: Inverse Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The method used in the paper was described in the study of Lauvaux et al (2012). The state vector (x) that includes the three components described above (daytime fluxes, nighttime fluxes and boundary inflow) is obtained by the following equation:…”
Section: Inverse Methodologymentioning
confidence: 99%
“…Though errors in the atmospheric transport model and at the boundaries limit the potential of the method (Go¨ckede et al, 2010b;Lauvaux et al, 2012), mesoscale inverse systems have shown consistent improvements from prior fluxes over short periods of time (Lauvaux et al, 2009), and at the annual time scale over the region (Schuh et al, 2010). Over longer time scales, the assessment of the regional flux balance implies the capability of capturing the spatio-temporal variability in the atmospheric CO 2 mixing ratios and avoiding persistent errors from the atmospheric transport models (e.g.…”
Section: Series B Chemical and Physical Meteorologymentioning
confidence: 99%
“…The boundary conditions have also been imposed based on independent data, such as aircraft in situ measurements (e.g. Brioude et al, 2012;Lauvaux et al, 2012;Wecht et al, 2014).…”
Section: Z Jiang Et Al: Regional Data Assimilation Of Multi-spectramentioning
confidence: 99%
“…For example, the fraction of the global CO 2 sink attributable to land versus ocean can be compared between inversions and independent model or mass-balance estimates (e.g., Le Quéré et al, 2015). For specific regions and periods, inversion results can also be compared against detailed inventory estimates of fluxes (e.g., Lauvaux et al, 2012;Schuh et al, 2013). A third example (noted already in Sect.…”
Section: Evaluation At Aggregated Scales Against Large-scale Scientifmentioning
confidence: 99%